Organochlorine Pesticide Residues in Sediments and Waters from Cocoa Producing Areas of Ondo State, Southwestern Nigeria. (20th March 2013) - Okoya, Aderonke Adetutu; Ogunfowokan, Aderemi Okunola; Asubiojo, Olabode Idowu; Torto, Nelson
Abstract : This study investigated levels of organochlorine pesticide (OCP) residues in water and sediment samples from eleven rivers serving as drinking water sources and receiving runoff from nearby cocoa plantations in Ondo State, Nigeria. Twenty-two composite samples of surface water and sediments (0–3 cm) were collected randomly using grab technique and replicated thrice per season. The efficiency of the two techniques [supercritical fluid extraction (SFE) and liquid/liquid extraction (LLE)] was evaluated with percentage analyte recoveries98.17  ±  0.03 to134.72  ±  0.02 for SFE and84.82  ±  3.32 to 1102.83  ±  3.17 for LLE. Determination of OCPs by gas chromatography with electron capture detection gave higher concentrations for sediments compared to the equivalent water samples. The commonly occurring pesticide residues in the sediments were (range, μ g g −1 ) cis-chlordane 0.03–6.99; α -endosulfan 0.03–6.99; p, p′-DDE 0.08–19.04; and dieldrin 0.01–7.62; in the sediments and dieldrin (not detected-1.51  μ g L −1 ) in water samples, during the dry season. OCP levels were significantly( P < 0.05 ) higher in dry season than wet season among the rivers. The study concluded that most of the rivers in cocoa growing areas were contaminated with OCPs associated with agricultural activities.